2015
DOI: 10.4238/2015.august.21.1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo determination of muscle-derived stem cells in rat corpus cavernosum

Abstract: ABSTRACT. The aim of this in vivo study was to determine the existence of muscle-derived stem cells (MDSCs) in rat corpus cavernosum. Immunohistochemical and RT-PCR analyses were performed to determine the expression of the stem cell markers (Sca-1, Oct4, and desmin) in Sprague-Dawley (SD) rats in different age groups (10 rats in each group). Sca-1 was mainly expressed in blood vessels and cavernous sinus and demonstrated primarily cytoplasmic staining. Desmin was expressed mainly in muscle tissues and stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…On the other hand, LESWT could enhance stem cell proliferation, differentiation and paracrine 44454647. In addition, the types of stem cells detected around the cavernous vasculature, including perisinusoidal and subtunic penile progenitor cells48 and cavernous smooth muscle-derived stem cells,4950 could be induced to activate. Thus, LESWT induced angiogenesis and created a beneficial situation for the establishment of the stem cell niche.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LESWT could enhance stem cell proliferation, differentiation and paracrine 44454647. In addition, the types of stem cells detected around the cavernous vasculature, including perisinusoidal and subtunic penile progenitor cells48 and cavernous smooth muscle-derived stem cells,4950 could be induced to activate. Thus, LESWT induced angiogenesis and created a beneficial situation for the establishment of the stem cell niche.…”
Section: Discussionmentioning
confidence: 99%
“…Yiou et al (2016) [44] studied the regenerative properties of MSCs and reported the ability of MSCs to repair multiple types of damage, especially those seen after RP. Also Xu et al (2015) [45] found that muscle-derived SCs in rat corpus cavernosum may have therapeutic potential in the treatment of organic ED. In a prevention study, Takayanagi et al (2015) [46] showed that i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Testosterone is an important inducer of stem cell differentiation [ 22 ], and endogenous muscle-derived stem cells have been detected in rat corpora cavernosa [ 23 ]. In vitro stem cell treatments can improve muscle content and decrease fibrosis in the corpora cavernosa [ 24 ].…”
Section: Discussionmentioning
confidence: 99%